2011
DOI: 10.1128/iai.00076-11
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and Progesterone Strongly Inhibit the Innate Immune Response of Mononuclear Cells in Newborns

Abstract: Newborns are particularly susceptible to bacterial infections due to qualitative and quantitative deficiencies of the neonatal innate immune system. However, the mechanisms underlying these deficiencies are poorly understood. Given that fetuses are exposed to high concentrations of estradiol and progesterone during gestation and at time of delivery, we analyzed the effects of these hormones on the response of neonatal innate immune cells to endotoxin, bacterial lipopeptide, and Escherichia coli and group B Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 45 publications
(62 reference statements)
9
104
0
4
Order By: Relevance
“…In contrast, E. coli leads to the secretion of much higher levels of TNF and IL-6 than GBS ( Fig. S2 A and B) (10), in agreement with the concept that MIF production is regulated differently than the production of classical proinflammatory cytokines (30,31). Of note, 24-h exposure to LPS increased MIF release 1.3-fold without affecting the intracellular MIF pool in newborn monocytes.…”
Section: Mif Plasmasupporting
confidence: 70%
See 2 more Smart Citations
“…In contrast, E. coli leads to the secretion of much higher levels of TNF and IL-6 than GBS ( Fig. S2 A and B) (10), in agreement with the concept that MIF production is regulated differently than the production of classical proinflammatory cytokines (30,31). Of note, 24-h exposure to LPS increased MIF release 1.3-fold without affecting the intracellular MIF pool in newborn monocytes.…”
Section: Mif Plasmasupporting
confidence: 70%
“…This suggests that whole microorganisms are more powerful than pure microbial products at inducing MIF release by monocytes. Estradiol, progesterone, and cortisol are present at high concentrations in the fetal and neonatal circulation (10). Exposure of newborn monocytes to estradiol, progesterone, and hydrocortisone at concentrations similar to those observed in the circulation at birth increased MIF secretion, implying that these hormones could participate in maintaining high levels of MIF in newborns (Fig.…”
Section: Mif Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Ces molécules diffusent dans la circulation foetale et influencent le système immunitaire du foetus et du nouveau-né. En effet, l'oestradiol et la progestérone inhibent l'activation de la voie de signalisation NF-B (nuclear factor-kappa B) ainsi que la production de TNF- (facteur de nécrose tumorale alpha) et d'IL(interleukine)-6 par des monocytes exposés à des bactéries coliformes [6]. L'adénosine et les prostaglandines PGE 2 et PGF 2 sécrétées par le placenta sont également présentes à des concentrations élevées dans la circulation Pendant la grossesse, le placenta (en rouge) produit en abondance des hormones stéroïdiennes, de l'adénosine et des prostaglandines (dont PGE 2 ) qui gagnent la circulation foetale par l'intermédiaire de la veine ombilicale (flèche jaune).…”
Section: Immunité Innée Néonataleunclassified
“…5,6 NK cells are broadly reactive against different kinds of virus, such as influenza virus, herpes viruses, hepatitis B virus and Marburg virus, indicating a general role of the cells in antiviral immune responses. [6][7][8] Antiviral cytokine expression is a main mechanism to inhibit virus replication and eliminate virus. Previous studies have demonstrated that NK cells from the peripheral blood had obvious secretion of interferon (IFN)-c and tumor-necrosis factor (TNF)-a against virus but low response in appropriate-for-gestational-age (AGA) neonates.…”
Section: Introductionmentioning
confidence: 99%